Ethanol sensitizes hepatocytes for TGF-β-triggered apoptosis - Gaitantzi, Haristi; Meyer, Christoph; Alborzinia, Hamed; Wölfl, Stefan; Ebert, Matthias; Breitkopf-Heinlein, Katja; Dooley, Steven (Cell death & disease, 2018)
Alcohol abuse is a global health problem causing a substantial fraction of chronic liver diseases. Abundant TGF-β - a potent pro-fibrogenic cytokine - leads to disease progression. Our aim was to elucidate the crosstalk of TGF-β and alcohol on hepatocytes. Primary murine hepatocytes were challenged with ethanol and TGF-β and cell fate was determined. Fluidigm RNA analyses revealed transcriptional effects that regulate survival and apoptosis. Mechanistic insights were derived from enzyme/pathway inhibition experiments and modulation of oxidative stress levels. To substantiate findings, animal model specimens and human liver tissue cultures were investigated. Results: On its own, ethanol had no effect on hepatocyte apoptosis, whereas TGF-β increased cell death. Combined treatment led to massive hepatocyte apoptosis, which could also be recapitulated in human HCC liver tissue treated ex vivo. Alcohol boosted the TGF-β pro-apoptotic gene signature. The underlying mechanism of pathway crosstalk involves SMAD and non-SMAD/AKT signaling. Blunting CYP2E1 and ADH activities did not prevent this effect, implying that it was not a consequence of alcohol metabolism. In line with this, the ethanol metabolite acetaldehyde did not mimic the effect and glutathione supplementation did not prevent the super-induction of cell death. In contrast, blocking GSK-3β activity, a downstream mediator of AKT signaling, rescued the strong apoptotic response triggered by ethanol and TGF-β. This study provides novel information on the crosstalk between ethanol and TGF-β. We give evidence that ethanol directly leads to a boost of TGF-β’s pro-apoptotic function in hepatocytes, which may have implications for patients with chronic alcoholic liver disease.